PENGARUH KREDIT BERMASALAH DAN TINGKAT KECUKUPAN MODAL TERHADAP PROFITABILITAS PERBANKAN YANG TERDAFTAR DI BEI TAHUN 2014 – 2017 - Ilmi Khairunisak; Noor Shodiq Askandar; Afifudin Afifudin (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTNon Performing Loan and The Effect of Capital Adequacy Ratio to ReturnOn Asset in Commercial Banking that Listed on Indonesian Stock ExchangePeriod 2014 - 2017This research aims to analyze the effect of the variable NPL and CARtoward ROA. This research using data from commercial banking publishedfinancial reports 2014-2017 period. The samples used were 20 commercial bankslisted in the Indonesia Stock Exchange in the period 2014-2017 were taken bypurposive sampling. Analysis technique used is analyzed multiple linearregression performed normality test and classical assumption test first.Conclusion from this research describe that NPL variable show negative andsignificant influence towards on ROA. CAR variables show positive and havesignificant effect with Return On Asset (ROA).Keyword : CAR, NPL, LDR, and ROA